Aplikasi Pembayaran SPP Pada TK Najma Ceria Berbasis Website - KIKI MARISA (ALMUISY: Journal of Al Muslim Information System, 2022)
This research is motivated by the problems faced by the administration section in recording monthly tuition payments which are still done manually so the school often loses the proof of payment that has been recorded. Then in making payment recapitulation reports it can be time-consuming, especially to determine a decision such as anyone who has not made a payment. The solution provided is to create and design a site-based educational operational fee payment applications, because it can minimize errors in recording transactions and generating reports that might occur if done manually. Based on the results of the trial this application can overcome and reduce problems that occur in the process of paying educational operational costs. In addition, this application also makes it easier for the administration section. If there are students who are late paying tuition, the system will automatically send notifications in the form of messages or e-mails to guardian parents. Keywords: Payment TK Najma Ceria